2018
DOI: 10.5194/aab-61-497-2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slaughter age and muscle type on meat quality characteristics of Eastern Anatolian Red bulls

Abstract: The effects of slaughter age and muscle type on meat quality properties of Eastern Anatolian Red (EAR) bulls (n = 46) were investigated in the present study. Forty-six EAR bulls were slaughtered at 15, 17, 19, 25 and 27 months. Meat samples were taken from longissimus dorsi (LD) and gluteus medius (GM) muscles obtained from the carcasses at 24 h post-mortem. Meat color parameters were significantly affected by slaughter age. Older animals (19, 25 and 27 months of age) possessed higher L * , a * and H values th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
6
11
1
1
Order By: Relevance
“…Overall acceptability increased with the increasing of age. Tenderness, juiciness, flavor intensity and overall acceptability increased until 19 months of age (Kopuzlu et al, 2018) which was similar to the present study. Pethick et al (2005) reported that there was no difference in the result of the tenderness and consumer tenderness on 12 months old lambs and 22 months old yearlings of Merino breeds.…”
Section: Effect Of Different Slaughter Ages On Sensory Attributes Of ...supporting
confidence: 91%
See 1 more Smart Citation
“…Overall acceptability increased with the increasing of age. Tenderness, juiciness, flavor intensity and overall acceptability increased until 19 months of age (Kopuzlu et al, 2018) which was similar to the present study. Pethick et al (2005) reported that there was no difference in the result of the tenderness and consumer tenderness on 12 months old lambs and 22 months old yearlings of Merino breeds.…”
Section: Effect Of Different Slaughter Ages On Sensory Attributes Of ...supporting
confidence: 91%
“…The 12 months lambs had significantly higher (p<0.001) saturation index (SI) value than that of 6 and 9 months aged lambs which indicates more color intensity. This result was similar to Kopuzlu et al (2018) where they stated that SI value increased with the increasing of age…”
Section: Effect Of Different Slaughter Ages On Instrumental Color Val...supporting
confidence: 88%
“…However, the results obtained by these authors indicated a greater value of shear force in the gluteus medius muscle than in the longissimus lumborum. The differences in the shear force depending on the type of muscles were recorded in lamb meat also by Esenbuga et al (2009) and by Kopuzlu et al (2018) in beef. According to Abdullah et al (2011), the variation in shear force values between muscles may result from differences in sarcomere length, muscle fiber types and their diameters.…”
Section: Physical Characteristics Of Meatsupporting
confidence: 52%
“…Mammalian muscles are composed of fibers of different morphological, metabolic and functional characteristics (Sazili et al, 2005). The development of various fiber types of muscle affects not only the overall muscle mass in carcasses of slaughter animals but also the quality traits of meat (Lee et al, 2010). The diversity of muscles, due to various proportions of each fiber type in them, may be related to intramuscular fat and connective tissue content, and also has an impact on meat color and water-holding capacity (Picard et al, 2002;Purslow, 2005;Yancey et al, 2005;Ryu and Kim, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The palatability of meat is influenced by tenderness and fat content, which are in turn affected by nutrition, muscle characteristics, post mortem events, genetics and the age of the animal 2 . Several studies have evaluated the impact of age on the tenderness and fatty acid profile of muscles in various species 3 , 4 . The dynamic synergy of genes and pathways in muscles in relation to age of the animal has also been explored in several species 5 – 7 .…”
Section: Introductionmentioning
confidence: 99%